2016
DOI: 10.1021/acs.inorgchem.5b02780
|View full text |Cite
|
Sign up to set email alerts
|

Ion Pair Binding in the Solid-State with Ditopic Crown Ether Uranyl Salophen Receptors

Abstract: Two ditopic uranyl salophen receptors with benzo-15-crown-5 and benzo-18-crown-6 units (R(1) and R(2), respectively) have been synthesized from commercially available starting materials. Comprehensive studies on the solid-state ion pair complexation with various alkali and ammonium halides have been conducted. From the 19 obtained solid-state structures (6 structures with R(1), 13 structures with R(2)), three general interaction motifs I-III have been observed. Interaction motif I has a separated ion pair with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Atoms U1 and U3 are both chelated between the two carboxylate groups of one c-1,2-chdc 2-ligand, bound to one more respectively, and Na1 is also coordinated to the uranyl oxo atom O1 with a bond length of 2.502 (11) Å, a value within the usual range for these rather common bonds. 21,[48][49][50][51][52][53][54] The packing displays an alternation of uranyl-containing polymeric sheets and layers occupied by the [Na(15C5)] + appendages. In the absence of water molecules, interactions between the sheets appear to involve largely CH···O contacts of the polyether units.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Atoms U1 and U3 are both chelated between the two carboxylate groups of one c-1,2-chdc 2-ligand, bound to one more respectively, and Na1 is also coordinated to the uranyl oxo atom O1 with a bond length of 2.502 (11) Å, a value within the usual range for these rather common bonds. 21,[48][49][50][51][52][53][54] The packing displays an alternation of uranyl-containing polymeric sheets and layers occupied by the [Na(15C5)] + appendages. In the absence of water molecules, interactions between the sheets appear to involve largely CH···O contacts of the polyether units.…”
Section: Resultsmentioning
confidence: 99%
“…One ligand group which provides these capabilities for the alkali metal ions is that of the crown ethers, 7 in that with the appropriate choice of ring size for the given metal ion, these can provide an essentially planar garland with divergently directed further coordination sites suited to a limited number of possible bridging modes of the metal ion. [8][9][10] Examination of the crystal structures reported in the Cambridge Structural Database (CSD, Version 5.38) 11 shows that crown ethers such as 12-crown-4 (12C4), 15-crown-5 (15C5), 18-crown-6 (18C6) and some of their derivatives have indeed proved useful in the construction of uranyl ion coordination polymers, [12][13][14][15][16][17][18][19][20][21] most often in their uncomplexed state, with only some cases involving a complexed alkali metal cation, either Na + or K + . 16,17,19,21 Most of these coordination polymers are based on inorganic ligands such as sulfates, selenates, chromates or phosphates, and only one case with a carboxylate ligand, 1,3-cyclohexanedicarboxylate, is known.…”
Section: Introductionmentioning
confidence: 99%
“…studied the fundamentals of selective recognition of uranyl ion by receptors such as antibodies, aptamers, DNAzymes, peptides, microorganisms and organic ionophores . The amino and phenolic groups on salophens have the function of providing electrons, and salophens are widely used to adsorb the transition metals and the main group metals, so uranyl‐salophens formed by the coordination of uranyl ion (UO 2 2+ ) with salophens have become a research hotspot . Recently, two new uranyl‐salophens were characterized where the uranyl ion formed a complex in a twisted planar configuration with a coordination number of four, and the tetra‐coordinated uranyl could still coordinate with other atoms or groups .…”
Section: Introductionmentioning
confidence: 99%
“…[10] The amino and phenolic groups on salophens have the function of providing electrons, and salophens are widely used to adsorb the transition metals and the main group metals, so uranyl-salophens formed by the coordination of uranyl ion (UO 2 2+ ) with salophens have become a research hotspot. [11][12][13] Recently, two new uranyl-salophens were characterized where the uranyl ion formed a complex in a twisted planar configuration with a coordination number of four, and the tetracoordinated uranyl could still coordinate with other atoms or groups. [14][15][16][17][18] Due to this particularity of the uranyl-salophens, their derivatives are widely used in molecular recognition, non-formation catalysis and enzyme construction.…”
mentioning
confidence: 99%
“…Recently we have studied the ion‐pair recognition of benzo[15]crown‐5‐ (B15C5) and benzo[18]crown‐6‐based (B18C6) bis‐urea receptors as well as the ion‐pair binding of B15C5‐ and B18C6‐based uranyl salophen receptors in the solid state . Comprehensive studies of the bis‐urea receptors in the solid state have revealed general characteristics of how these types of molecules behave, depending on the nature of the ion pairs, and how the crown ether size affects to the ion pair recognition modes.…”
Section: Introductionmentioning
confidence: 99%